Changing hearts
1 online resource.
Keywords: This volume of essays contributes to our understanding of the ways in which the Jesuits employed emotions to “change hearts”—that is, convert or reform—both in Europe and in the overseas missions. The early modern Society of Jesus excited and channeled emotion through sacred oratory, Latin poetry, plays, operas, art, and architecture; it inflamed young men with holy desire to die for their faith in foreign lands; its missionaries initiated dialogue with and ‘accommodated’ to non-European cultural and emotional regimes. The early modern Jesuits conducted, in all senses of the word, much of the emotional energy of their times. As such, they provide a compelling focus for research into the links between rhetoric and emotion, performance and devotion, from the sixteenth through eighteenth centuries.